Experimental Study of Hollow-core Slab Containing Waste PET Bottles - Orientilize, Mulia; Rastandi, Josia Irwan; Aries C., R. M. Dimas; P., Marsha Niken; S.S., Krisna Adi; Abimantrana, Abimantrana (UI Scholars Hub, 2021)
This study investigated the utilization of plastic-waste concrete as an effort to reduce urban waste problems. The waste plastic bottles were utilized to form the hollows of the hollow-core slabs (HCSs). The bottles were made of polyethylene terephthalate (PET). As a part of green research to reuse waste material, shredded PET was also added to the concrete mixture to improve the HCS strength. The cast-in-site HCS could be constructed without any difficulties. Three parameters were investigated: the effects of void content, shredded PET content, and steel-fiber (SF) content on the HCS ultimate bending capacity (Mu). Fifteen specimens were tested under static loads until failure, and the results were compared with those of the solid slab. Two different void contents 19% and 24% were studied. The other parameters were the shredded PET content (0.5% and 0.7%) and the SF content (0.19% and 0.32%). The Mu values of the HCS specimens were 12% to 16% less than that of the solid slab. However, the strengths were still within the theoretical capacity of the slab. The addition of the shredded PET could improve the HCS bending capacity by 18% to 38% compared with that of the solid slab. Similar results were also found for the specimens with SFs, whose Mu values were 11% to 46% greater than that of the solid slab.